The development of bioinformatics knowledge management system with collaborative environment. - Abdullah, Rusli; Ibrahim, Hamidah; Atan, Rodziah; Napis, Suhaimi; Selamat, Mohd Hasan; Hairudin, Nurul Haslina; Hamidon, Siti Hernazura (International Journal of Computer Science and Network Security, 2008)
Nowadays, Knowledge Management System (KMS) becomes a common medium to distribute knowledge by using the IT as enabler tools for everyone to reach, share with among the members, and used it from any workplace in the world at any time. In the context of Bioinformatics institution sectors, the collaboration tools of KMS explore the opportunity to create, gather, access, organize, distribute and disseminate the knowledge to their community of practice (CoP) for various purposes such as learning process, Research and Development (R & D) and others. This paper describes on the theoretical concepts and approach of Bioinformatics KM system that could be implemented in institution by showing on how the framework of KM system model is developed using relevance software. The achievement in conducting this framework of the Bioinformatics KMS is an added value for the institution that needs to implement the Bioinformatics KMS, which can help them to achieve their aims and mission statements. The emphasis also will be given to the activities for each stage in the KM life cycle including the critical success factor (CSF) in order to make sure that KMS initiatives will deliver competitive advantage to the institutions.